Mortalidade entre adolescentes de Feira de Santana, Bahia: estudo de série temporal - Carneiro, Dailma Ferreira (2018)
Introduction–In adolescence, the mortality rate for external causes is high, especially in the age range from 15 to 19 years old, with greater exposure to risk situations. The experience in poor and/or stigmatized communities, without access to public services and on the effect of social inequalities, it may cause greater vulnerability to the causes of death in general and the external causes of death in particular. Objective – describing the mortality profile of teenagers between 10 to 19 years, according to sociodemographic variables and causes groups, in Feira de Santana, Bahia, from 2007 to 2016. Methods – Descriptive time series study that analyzed the data of the Mortality Information System (MIS), from 2007 to 2016, concerning the population in the age group of 10 to 19, residents in Feira de Santana, Bahia. The causes of deaths have been identified and the mortality rates and their death incidence curves by age group and death cause were calculated. Results – Homicide was the cause of death that prevailed among teenagers aging from 10 to 19, male, race/skin color: brown and black, with low schooling. With regard to non-external causes, neoplasms were highlighted in both age groups. The death coefficient for murder was 62,5/100,000 in 2007 and reached 92,7/100,000 in 2015, with a peak of 149,4/100,000 in 2010, in the age range of 15 to 19. Conclusion – It was observed that in the age range of 15 to 19, the external causes were the most frequent, highlighting the murders, and, among the non-external causes, the neoplasms. Thus, most deaths in this age group can be avoided by adopting preventive and health education measures, by means of public policies, focused on the studied age group and the greater commitment of the Public Health Department and Public Security Department.